2020
DOI: 10.1016/j.jmb.2020.02.008
|View full text |Cite
|
Sign up to set email alerts
|

3,6-Anhydro-L-Galactose Dehydrogenase VvAHGD is a Member of a New Aldehyde Dehydrogenase Family and Catalyzes by a Novel Mechanism with Conformational Switch of Two Catalytic Residues Cysteine 282 and Glutamate 248

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…30 The residues that make up the substrate pocket determine the physicochemical properties of the substrate, such as its charge, shape, and size. 9 By determining the substrate pocket of the enzyme and formulating effective transformation strategies, the enzyme's catalytic rate, specificity, and promiscuity can be optimized. 31 Zhou et al used the "polarity scanning" strategy to adjust the charge properties in the substrate pocket of alcohol dehydrogenase, and mutants with enhanced and inverted stereoselectivity were obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…30 The residues that make up the substrate pocket determine the physicochemical properties of the substrate, such as its charge, shape, and size. 9 By determining the substrate pocket of the enzyme and formulating effective transformation strategies, the enzyme's catalytic rate, specificity, and promiscuity can be optimized. 31 Zhou et al used the "polarity scanning" strategy to adjust the charge properties in the substrate pocket of alcohol dehydrogenase, and mutants with enhanced and inverted stereoselectivity were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…In most enzymes, the substrate pocket is the core region to perform catalytic functions . The residues that make up the substrate pocket determine the physicochemical properties of the substrate, such as its charge, shape, and size . By determining the substrate pocket of the enzyme and formulating effective transformation strategies, the enzyme’s catalytic rate, specificity, and promiscuity can be optimized .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the role of Cys-293 in the SCO3486 protein is expected to be important among the four catalytic residues. Moreover, recent studies on three-dimensional structures of AHG dehydrogenase revealed that Glu-259 and Cys-293 are important for its catalytic activity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bioconversion of AHG is a bottleneck for red algae fermentation since AHG is a rare and untapped sugar. In recent years, researchers have discovered more of the AHG metabolic pathway and continue to develop related enzymes in this pathway to provide more options for metabolic engineering. The proposed AHG pathway starts from converting AHG to AHGA through the oxidation of an aldehyde group . AHGA is then isomerized to form KDGal by AHGA cycloisomerase.…”
Section: Biotransformation Of Macroalgae Polysaccharidesmentioning
confidence: 99%